Retrospective cohort study of morphological features of recurrent schwannomas and neurofibromas - D. A. Murzaeva; Yu. M. Zabrodskaya; A. A. Dolgushin; L. N. Dobrogorskaya; A. Y. Orlov (Сеченовский вестник)
Recurrences of benign peripheral nerves sheaths tumours (BPNST) after total resection were described in 2.6–11.0% of patients. The significance of the histological features of recurrent BPNST is still insufficiently studied.Aim. To compare the pathomorphological features of recurrent and non-recurrent BPNST (schwannomas and neurofibromas).Materials and methods. A retrospective assessment was made of 101 patients with BPNST with a degree of anaplasia corresponding not more than Grade I. Recurrence of BPNST developed in 13 (12.9%) cases. The study included patients with histological archive: the study group (n = 7) included patients with one or more relapses of BPNST, the control group included patients (n = 5) without relapses after surgery for 5 or more years. The main clinical characteristics were studied and histological examination was performed.Results. There were no differences between the groups in baseline characteristics (the type of tumour (schwannoma, neurofibroma), distribution by sex, age, localization, clinical symptoms). The relapse rate among patients with neurofibromas was 8 in 3 patients vs. 6 in 5 patients with schwannomas. In all cases of recurrent schwannomas and in one of neurofibroma, the histological pattern was predominantly monophasic with rhythmic structures like Verocay bodies with underlined pattern and nuclear hyperchromasia, in contrast to the control group, represented by tumours with a mixed type of structure with uniform alternation of various histological patterns (p < 0,05). Endothelial proliferation and lymphocytic infiltration in the stroma and perivascular area were more common in the relapse group (p < 0.05). Pathomorphological signs of anaplasia: cell-nuclear polymorphism, nuclear hyperchromasia, endothelial proliferation, mitosis, as well as minor signs of anaplasia: solidization, muirization of the fascicular pattern of a tumour and apoptotic bodies were found with the same frequency in both groups. With relapse, the capsule was lost, thinned, intermittent, and sometimes invaded the surrounding tissues.Conclusion. Tumours with the initial signs of anaplasia, such as endothelial proliferation, tendency to hypercellularity, and histological pattern with prominent Verocay bodies dominate among recurrent BPNST.